Maternal density stress and coccidian parasitism: Synergistic effects on overwinter survival in root voles. (22nd May 2018) - Yang, Yan‐Bin; Shang, Guo‐Zhen; Du, Shou‐Yang; Zhang, Xin; Wu, Yan; Bian, Jiang‐Hui
Abstract: Individuals in poor physiological condition are known to be more susceptible to infection that, once it occurs, further deteriorates the individuals' conditions, making them even more susceptible to infection and leading to death. This vicious synergy between the host condition and infection has recently been proposed to be among the key factors determining the oscillation characteristics in natural populations. Field studies that directly test such a hypothesis, however, are currently scarce, and the physiological traits involved remain largely unclear. In this field study, we systematically examined the synergistic effects of maternal stress and coccidian parasitic interaction on the physiological conditions and overwinter survival of offspring in the root vole ( Microtus oeconomus ) via repeated live trapping and measurements of faecal corticosterone metabolite (FCM) levels and immunocompetence in captured animals. We found that maternal density stress significantly increased FCM levels and both the prevalence and intensity of coccidian infection in offspring, significantly suppressed offspring immunocompetence and reduced offspring overwinter survival. Coccidian infection significantly potentiated increases in FCM levels and exacerbated the immune suppression induced by maternal density stress. Coccidian infection also significantly accelerated a decrease in overwinter survival and a population decline in maternal‐density‐stressed populations. Our findings indicate that both stress and immune systems are involved in the synergistic process through which stressors and parasites interact with the host to influence the fitness of individuals and cause a population decline in the natural environment. A plain language summary is available for this article. Abstract : Plain Language Summary